PP.66 An Audit of Reduced Fetal Movements in a District General Hospital in Lanarkshire. (26th April 2013) - Kellison, LR; Ferguson, E; Wolff, O
Abstract : Background: Fetal movements are perceived as a sign of a fetal wellbeing, with reduced fetal movements (RFM) associated with poor perinatal outcome. Antenatal investigation of RFM aims to exclude fetal death and identify pregnancies at risk of adverse outcomes. Wishaw General does not currently have a local RFM guideline. Aims: To audit the management of women presenting to Wishaw General Maternity Unit (WGMU) with RFM, compare with RCOG guidance and devise a local RFM guideline. Method: A retrospective case note review of 23 patients presenting to WGMU. Results: 13 primigravid and 10 parous women, with a mean gestation of 37 weeks (24–41), were included. Based on KCND 11 were high risk and 12 low risk. All women received CTG investigation, 100% were normal. There was no documentation of risk factors for IUFD or of fundal height measurement at presentation. 4% of women were booked for USS within 24 hours of presenting with RFM. Induction of labour for RFM occurred in 4% of patients presenting at term. All had live births with no NNU admissions. There were no infants <2.5 kg. Conclusion: 82% (14) of women were not scanned who met criteria for referral. 35% (8) of women had no form of follow up arranged. Currently our unit is failing to meet the RCOG recommendations of Greentop Guideline 57. We have developed a local guideline to improve management of women with RFM and re-audit is underway. Reference: RCOG Greentop Guideline 57; Reduced Fetal Movements. February 2011.